BACTERIAL ISOLATIONIN CANINE EAR INFECTIONS AND ITS ANTIMICROBIAL SUSCEPTIBILITY - Sánchez Ch., Ricardo (2011)
The objective of the study was to determine the frequency of bacterial otitis cases indogs, the bacteria involved in the infection and the bacterial susceptibility to antibioticsin samples processed during 2001-2006 in a bacteriology laboratory specialized in theveterinary field. A total of 429 laboratory records were used. The most frequent isolatedbacteria was Staphylococcus intermedius (27.7%), but other important species were alsofound (Pseudomonas aeruginosa, Streptococcus sp. and Staphylococcus sp). Earinfections were mostly due to a single bacteria species (63.6%). In susceptibility testusing the Kirby-Bauer method the quinolones, aminoglycosides, cephalosporins, and penicillins combined with inhibitors of betalactamics showed better antimicrobial effect,while bacteria species showed high resistance to penicillin, sulpha, tetracyclines,macrolides and lincosamides.